Evolving Coagency between Artists and AI in the Spatial Cocreative Process of Artmaking - Nordström, Paulina; Lundman, Riina; Hautala, Johanna (Taylor & Francis, 2023)
This article applies theoretical and empirical discussions of emerging human and digital technology relations to our interest in collaborative artist–artificial intelligence (AI) artmaking processes. Thus far, the theoretical focus has largely been on mediating (code) and merged (cyborg) human–technology relations, with mutual (coagency) relations yet to be adequately explored. To address this, we nuance the theoretical discussion and extend the empirical research, analyzing the spatial cocreative artmaking process through video interviews with eighteen Finnish artists using AI. Drawing on the work of Barad, we regard humans and AI as fundamentally entwined, receiving their agencies through intra-action. Building on this, we demonstrate how the agencies of artists and AI emerge and mutually evolve across three stages of the creative process: (1) coding and data, (2) learning and training, and (3) curating the outcome. Thus, through our empirical research on how artist and AI create new material and meaningful artworlds, we are able to nuance understanding of coagency as a spatial process.

本文将新兴的人类和数字技术关系的理论和实证讨论, 应用于艺术家-人工智能(AI)的合作艺术创作过程。迄今为止, 理论研究的主要重点是调节(代码)和融合(电子人)人与技术关系, 没有对相互(协作)关系进行充分讨论。为此, 我们开展了详尽的理论研究, 扩展了实证研究。基于对使用人工智能的18位芬兰艺术家的视频采访, 分析了艺术的空间合作创作过程。根据巴拉德的研究, 我们认为, 人类和人工智能本质上是交织在一起的, 并产生内作用。在此基础上, 我们展示了艺术家和人工智能的作用如何出现于并相互演化于创作的三个阶段: (1)编程和数据, (2)学习和训练, (3)策划结果。通过对艺术家和人工智能如何创造新材料和艺术世界的实证研究, 我们得以详尽理解协作的空间过程。

Este artículo aplica las discusiones teóricas y empíricas de las relaciones emergentes entre los humanos y la tecnología digital a nuestro interés en los procesos colaborativos de producción estética entre el artista y la inteligencia artificial (IA). Hasta este momento, el foco teórico en gran medida se ha centrado en las relaciones humano-tecnológicas mediadoras (código) y ligadas (cíborg), con las relaciones mutuas (coagencia), todavía sin exploración adecuada. Para abordar este asunto, matizamos la discusión teórica y extendemos la investigación empírica, analizando el proceso espacial de producción artística cocreativa por medio de entrevistas en vídeo con dieciocho artistas finlandeses que usan IA. Basándonos en el trabajo de Barad, consideramos que los humanos y la IA están fundamentalmente entrelazados, recibiendo los efectos de sus agencias a través de la intra-acción. A partir de lo anterior, demostramos cómo las agencias de los artistas y la IA emergen y evolucionan mutuamente a través de tres etapas del procesos creativo: (1) codificación y datos, (2) aprendizaje y entrenamiento y (3) curaduría del resultado. Así, por medio de nuestra investigación empírica sobre cómo el artista y la IA crean nuevos materiales y mundos de arte significativos, nos habilitamos para matizar el entendimiento de la coagencia como un proceso espacial.
Keywords: agency; art; artificial intelligence; cocreativity; digital geographies; fi=Aluetiede|en=Regional Studies|